Artikel Review: Kajian Efektivitas Tanaman Eucalyptus Globulus Untuk Mencegah Komorbid Penyakit COVID-19 - Vriezka Mierza; Nur Komala Fitri; Priscinya Christiana Debora; Saarah Hamidah Asmara Indratno; Tiwi Ambarati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Eucalyptus globulus, a plant that produces essential oils by distilling its leaves, has been studied in the context of preventing comorbid diseases of Covid-19. Through literature searches on Google Scholar and Pubmed with the keywords